2022
DOI: 10.3390/ijms23137319
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of miRNA Expression Profiling of RIP2 Knockdown in Chicken HD11 Cells When Infected with Avian Pathogenic E. coli (APEC)

Abstract: Colibacillosis is an acute and chronic avian disease caused by avian pathogenic E. coli (APEC). Previous studies have demonstrated that RIP2 plays a significant role in APEC infection. Moreover, increasing evidence indicates that microRNAs (miRNAs) are involved in host–pathogen interactions and the immune response. However, the role of miRNAs in the host against APEC infection remains unclear. Herein, we attempted to reveal new miRNAs potentially involved in the regulation of the immune and inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…MicroRNAs (miRNAs) are small noncoding RNAs that modulate gene expression at the posttranscriptional level either by inhibiting mRNA translation or by promoting mRNA degradation ( Correia de Sousa et al., 2019 ). As essential regulators, many miRNAs are involved in regulating pathological and physiological processes after APEC infection ( Jia et al., 2016 ; Sun et al, 2022a ; Yin et al., 2022 ). Several studies have suggested that the miRNA expression profile may be a valuable biomarker for the diagnosis, prognosis, and prediction of response to therapy, as well as a powerful tool for disease prevention and treatment ( Jia et al., 2016 ; Hrach and Mangone, 2019 ; Becker et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs that modulate gene expression at the posttranscriptional level either by inhibiting mRNA translation or by promoting mRNA degradation ( Correia de Sousa et al., 2019 ). As essential regulators, many miRNAs are involved in regulating pathological and physiological processes after APEC infection ( Jia et al., 2016 ; Sun et al, 2022a ; Yin et al., 2022 ). Several studies have suggested that the miRNA expression profile may be a valuable biomarker for the diagnosis, prognosis, and prediction of response to therapy, as well as a powerful tool for disease prevention and treatment ( Jia et al., 2016 ; Hrach and Mangone, 2019 ; Becker et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another research article by the same research group further reported new microRNAs (miRNAs) that are potentially involved in the modulation of the APEC infection-induced inflammatory response. This study identified gga-miR-445-5p, which is differentially regulated by RIP2, and demonstrated that gga-miR-445-5p played a critical role in the inflammatory response against APEC infection via targeting IRF2 to regulate type I interferons expression [ 14 ].…”
mentioning
confidence: 99%